Sialic Acid-Siglec-E Interactions During Pseudomonas aeruginosa Infection of Macrophages Interferes With Phagosome Maturation by Altering Intracellular Calcium Concentrations - Mukherjee, Kaustuv; Khatua, Biswajit; Mandal, Chitra (Frontiers in Immunology, 2020)
Pseudomonas aeruginosa (PA) is commonly associated with nosocomial and chronic infections of lungs. We have earlier demonstrated that an acidic sugar, sialic acid, is present in PA which is recognized and bound by sialic acid binding immunoglobulin type lectins (siglecs) expressed on neutrophils. Here, we have tried to gain a detailed insight into the immunosuppressive role of sialic acid-siglec interactions in macrophage-mediated clearance of sialylated PA (PA+Sia). We have demonstrated that PA+Sia shows enhanced binding (~1.5 fold) to macrophages due to additional interactions between sialic acids and siglec-E and exhibited more phagocytosis. However, internalization of PA+Sia is associated with a reduction in respiratory burst and increase in anti-inflammatory cytokines secretion which is reversed upon desialylation of the bacteria. Phagocytosis of PA+Sia is also associated with reduced intracellular calcium ion concentrations and altered calcium-dependent signaling which negatively affects phagosome maturation. Consequently, although more PA+Sia was localized in early phagosomes (Rab5 compartment), only fewer bacteria reach into the late phagosomal compartment (Rab7). Possibly, this leads to reduced phagosome lysosome fusion where reduced numbers of PA+Sia are trafficked into lysosomes, compared to PA-Sia. Thus, internalized PA+Sia remain viable and replicates intracellularly in macrophages. We have also demonstrated that such siglec-E-sialic acid interaction recruited SHP-1/SHP-2 phosphatases which modulate MAPK and NF-κB signaling pathways. Disrupting sialic acid-siglec-E interaction by silencing siglec-E in macrophages results in improved bactericidal response against PA+Sia characterized by robust respiratory burst, enhanced intracellular calcium levels and nuclear translocation of p65 component of NF-κB complex leading to increased pro-inflammatory cytokine secretion. Taken together, we have identified that sialic acid-siglec-E interactions is another pathway utilized by PA in order to suppress macrophage antimicrobial responses and inhibit phagosome maturation, thereby persisting as an intracellular pathogen in macrophages.